2D Material Based Advanced Membranes for Separations in Organic Solvents. Issue 50 (20th November 2020) - Sui, Xiao; Yuan, Ziwen; Yu, Yanxi; Goh, Kunli; Chen, Yuan
Abstract: 2D materials have shown high potentials for fabricating next‐generation membranes. To date, extensive studies have focused on the applications of 2D material membranes in gas and aqueous media. Recently, compelling opportunities emerge for 2D material membranes in separation applications in organic solvents because of their unique properties, such as ultrathin mono‐ to few‐layers, outstanding chemical resistance toward organic solvents. Hence, this review aims to provide a timely overview of the current state‐of‐the‐art of 2D material membranes focusing on their applications in organic solvent separations. 2D material membranes fabricated using graphene materials and a few representative nongraphene‐based 2D materials, including covalent organic frameworks and MXenes, are summarized. The key membrane design strategies and their effects on separation performances in organic solvents are also examined. Last, several perspectives are provided in terms of the critical challenges for 2D material membranes, including standardization of membrane performance evaluation, improving understandings of separation mechanisms, managing the trade‐off of permeability and selectivity, issues related to application versatility, long‐term stability, and fabrication scalability. This review will provide a useful guide for researchers in creating novel 2D material membranes for advancing new separation techniques in organic solvents. Abstract : 2D materials are promising material candidates for next‐generation membranes due to their unique properties. Several 2D materials, including graphene and nongraphene‐based materials, as membrane materials for organic solvent separation, are reviewed. The critical challenges are discussed to provide a perspective on developing novel 2D material membranes for advancing organic separation techniques.